Acharya J.C. Bose, a scientist & a dreamer : Volume-5 - Bose, Jagadis Chandra; Bhattacharyya, Prantosh; Engineer, M. H.; Das Gupta, Arun Kumar; Mitra, Rukmini; Bose Institute (Kolkata, India) (Calcutta : Bose Institute, 1997)
An account of the scientific works of Jagadis Chandra Bose.
v. 1. Covers the period 1895-1918 -- v. 2. Covers the period 1919-1921 -- v. 3. Covers the period 1924-1934 -- v. 4. Comprises of his speeches, selected letters, and articles -- v. 5. Letters to Rabindranath Tagore.
Includes bibliographical references.
Includes one paper in French.
Keywords: Botany; Physics